Orobanche alba subsp. alba and subsp. major (Orobanchaceae) in Poland: current distribution, taxonomy, plant communities, hosts, and seed micromorphology - Piwowarczyk, Renata (Biodiversity: Research and Conservation, 2012)
The paper presents the current distribution of Orobanche alba subsp. major and subsp. alba in Poland, based on a critical revision of herbarium and literature data as well as results of my field studies. Most of their localities are in southeastern Poland: in the Małopolska Upland, Lublin Upland, Roztocze Hills, Polesie, Przemyśl Foothills (Pogórze Przemyskie), and Western Bieszczady Mts. These are the northernmost sites known for the species in Central Europe, so the new data extend its distribution range. Maps of distribution of both the subspecies in Poland and of subsp. major in Central Europe are included. Additionally, their seed micromorphology was compared using scanning electron microscopy (SEM). The taxonomy, biology, and ecology of both the subspecies of O. alba are also discussed.